Organizational Culture and Innovative Work Behavior: Knowledge Sharing as a Mediator in Indonesian SMEs - Karima, Billah; Salendu, Alice; Azzahra, Fadia (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2026)
Grounded in the Competing Values Framework, this study examines how organizational culture (adhocracy, clan, and market) influences innovative work behavior (IWB) among employees in Indonesian SMEs, with knowledge sharing as a mediating mechanism. A quantitative cross-sectional survey of 185 SME employees was analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). Results indicate that clan culture exerts the strongest direct effect on IWB (β = .307, p < .001), followed by adhocracy culture (β = .241, p = .002) and market culture (β = .226, p < .001). Knowledge sharing significantly mediates all three culture-IWB relationships (adhocracy: β = .264; clan: β = .236; market: β = .196; all p < .05). These findings underscore the pivotal role of knowledge-sharing practices in translating organizational culture into employee innovation, with practical implications for SME management in developing economy contexts.